Termorregulación y eficiencia de intercepción de luz en Opuntia pilifera Weber (Cactaceae) - Cano-Santana, Zenon; Cordero, Carlos; Ezcurra, Ezequiel (Instituto de Ecología, A.C., 1992)
The orientation of photosynthetic surfaces affects the interception of photosynthetically active radiation (PAR), as well as the temperatura of the photosynthetic tissues. Plante face the problem of displaying their photosynthetic surfaces in order to obtain adequate levels of PAR interception without reaching dangerously high temperatures. In the Zapotitlan Valley, Puebla  (México), Opuntia pilifera cladodes exposed to direct solar  radiation have inclinations chiefly between 80° and 90fl, as well  as a preference for an E-W orientation. This pattern is less  marked in shaded plante, in which dadode inclination is more variable and which do not present a preferred azímuth. Given  the geographic location and climate of the study area, the  spatial display of O. pilifera cladodes is interpreted as an  adaptive solution to the conflict between PAR interception and thermoreguiation.